High‐level MYC expression associates with poor survival in patients with acute myeloid leukemia and collaborates with overexpressed p53 in leukemic transformation in patients with myelodysplastic syndrome. (19th August 2020) - Gao, Linlin; Saeed, Azhar; Golem, Shivani; Zhang, Da; Woodroof, Janet; McGuirk, Joseph; Ganguly, Siddhartha; Abhyankar, Sunil; Lin, Tara L.; Cui, Wei
Abstract: Introduction: Patients with mutated and overexpressed p53 have an aggressive course in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Studies on the impact of MYC expression in AML are limited. This is the first study to evaluate MYC expression and p53 status in AML and MDS. Methods: We identified 214 patients, 101 AML, 79 MDS,  and 34 negative control patients. We retrospectively assessed p53 and MYC expression by immunohistochemistry and correlated MYC expression with p53 expression and aberrational status of TP53 . Results: The level of both p53 and MYC expression was significantly higher in AML (mean: 9.7%; 12.1%) and MDS (mean: 5.2%; 5.5%) patients compared with control cases (mean: 0.18%; 2.3%; P  = .001‐0.02). p53 and MYC expression levels were even more elevated in AML when compared to MDS patients ( P  < .001). MYC expression was significantly associated with p53 expression and TP53 aberration in AML patients but not in MDS patients ( P  < .001). p53 expression and >20% MYC expression showed an adverse impact on overall survival (OS) ( P  < .05) in AML patients while p53 but not MYC expression showed an adverse impact on OS in MDS patients. MYC and p53 dual expression, as well as combined MYC expression and TP53 aberration, showed negative impact on OS in AML patients. MDS patients with leukemic transformation revealed an interval increase in expression of both p53 and MYC. Conclusion: High‐level MYC expression associates with p53 abnormality and poor survival in AML. MYC may provide proliferative advantage for leukemic progression in p53 dependent and independent manner.